Pengaruh variasi sumber kalor terhadap besarnya laju perpindahan kalor melalui dinding komposit - Rudi Hariyanto; Mohamad Ma'ruf (Jurnal Penelitian, 2003)
Heat transfer is the study of how heat moves or flows from a place with a high temperature to a lower temperature so that heat can move due to a "temperature difference". There are three types of heat transfer, but for heat flow through composite materials, heat transfer analysis uses conduction heat transfer analysis. The rate of heat transfer through the composite material will vary depending on several parameters such as material properties, surface area, material thickness, and other parameters. Research to find out how big the influence of heat source variations on the rate of heat transfer through the composite wall resulted in the conclusion that the heat transfer rate also increased in proportion to the increase in the heat source. However, the use of composite walls in series causes the overall heat transfer rate to decrease because it is influenced by the thickness of the material. The thicker the material, the lower the heat transfer rate.